Advances in the Mechanization of Regenerating Plantation Forests: a Review - Ramantswana, Muedanyi; Guerra, Saulo Philipe Sebastiao [UNESP]; Ersson, Back Tomas (Springer, 2020)
Purpose of Review The mechanization of silvicultural work on forest plantations is usually driven by a decreasing supply of motivated labour which increases its relative cost. Mechanization can also result in other advantages like increased effectiveness, higher efficiency, and improved working conditions. The purpose of our review is to examine the last few decades' endeavours to mechanize the regeneration activities of plantation forestry in the southern and northern hemisphere. In this case, regeneration activities include (1) site preparation; (2) tree planting; and (3) stand tending until the crop trees are free from vegetative competition. Recent Findings Originally, the mechanization of silvicultural work commenced in the northern hemisphere, but over the past decades, the most notable progress has been made in the southern hemisphere plantation forests. Although soil preparation is largely mechanized across the globe, tree planting and stand tending activities lag behind because of factors such as global variations in the manner in which they are performed, higher level of complexity, and low-cost competitiveness compared with existing labour-intensive methods. For mechanization of regeneration/silvicultural activities to progress, productive and adaptable machines will be required where economies of scale permit cost-efficient operations. These machines will probably have to be modified to the specific forestry context of different countries. Knowledge of the existing and state-of-the-art regeneration technologies available in both the northern and southern hemispheres is important for foresters to make informed decisions about the selection and application of mechanized regeneration systems.
Keywords: Forest operations; Silvicultural technology; Site preparation; Tree planting; Stand tending; Reforestation